Modelo de governan??a de seguran??a da informa????o para a Administra????o P??blica Federal - Guimar??es, Rog??rio (2016)
The governance of information security and communication is a set of policies and processes which allows the institutions, public and private, to monitor, evaluate and direct its information assets management, therefore reducing risks against its integrity, confidentiality and availability, aligned with the business necessities, and increasing value, accomplishing benefits, mitigating risks and optimizing costs. This study aims to propose a framework of information security and communication governance for the Federal Government, adhering to Brazilian legal standards and compatible with the Information Security and Communication Strategy and Cybersecurity of the Public Federal Government 2015 ??? 2018, version 1.0. The literature review unveiled the lack of studies about information security and communication governance directed to the Federal Government. From the content analysis, considering specific criteria, and the DSIC ??? Information Security and Communication presidential department ??? norms, as well as the standard NBR ISO/IEC 27002:2013, and the NIST ??? National Institute of Standards and Technology ??? model, the proposed framework was submitted to the analysis of information security specialists of the Government (focus group). The aims of this study were achieved. However, it is expected, moreover, that the present study is able to promote and encourage new studies on the subject.